Cultural values as institutional forces in shaping board involvement. - Lim, Boon Yeow (Asian online journals, 2015)
The paper examines the importance of Chinese cultural values as a useful “societal-institutional” framework for understanding the patterns of involvement of board members in Chinese firms and its performance. Its richness are apparent at macro level, examining the relationship between Chinese characteristics and organization structure, and at the micro level for investigating the similarities and differences in attitude of board members with given characteristics. The cultural perspectives at both micro and macro levels able to offer complementary views of Chinese board behavior. This paper offers the first step in explaining the important role of cultural values as institutional forces in legitimizing the organization’s existence and its modes of functioning as well as the patterns of behavior of its board members.